(untitled) (Journal of Science, Technology and Innovation Policy, 2023)
Capacity building is critical to the success and sustainability of cottage industries. It helps to improve the skills and knowledge of workers, increase productivity and efficiency, strengthens business practices, develop an entrepreneurial mind-set, and create a supportive business environment. Therefore, the aim of current study is to explore the relationship between capital access and cottage industry growth, to analyse the relation and importance of education and awareness with cottage industry growth and to explore the relation between technology and growth of cottage industry in Pakistan. The sample size of this quantitative study is 280 including Pakistani small entrepreneurs in Punjab. This study applied Anova test for data analysis by using SPSS. The framework shows that three factor can improve or reduce the growth of cottage industry such as education, technology, and capital access. The results of this study are in accordance with other similar studies which show that the model is feasible and the relationship exists positively and strongly between the variables selected. The government must also focus on opening more educational and training institution to improve the skills of people regarding opening cottage industries. This way, the small businesses industry will be able to absorb the problems and the lack of capital shocks. Cottage industry entrepreneurs should be given access to international markets and provisions should be made to link them with distributers and sellers.